Knowledge, Attitudes, and Beliefs about Dilated Eye Examinations among African-Americans - Ellish, Nancy J. (2007)
PURPOSE: To understand factors that influence African-Americans’ attitude toward eye examinations. METHODS: Ten focus groups were conducted with 86 African-Americans. Four focus groups were conducted with people 65 years of age and older who had not received a dilated fundus examination (DFE) in the past 2 years, two groups were held with people 65 years of age and older who had had a recent DFE, and two groups each were held with people 40 to 64 years of age, with and without recent DFEs. Focus group interviews were conducted by using a moderator guide to address perceived benefits of and barriers to getting an eye examination; motivators for getting DFEs; and knowledge of eye examinations, glaucoma, and diabetic retinopathy. Participants also completed a questionnaire that provided demographic information. Quantitative and qualitative analyses were conducted. RESULTS: Cost or lack of sufficient insurance was identified as the most important barrier to getting a DFE. Also frequently mentioned was not having any symptoms and being too busy. The most frequently cited benefit of getting a DFE was to help prevent eye disease, whereas the most frequently reported motivating factor was experiencing a vision problem. Regarding knowledge, many people did not know the risk factors for glaucoma, but seemed to have a better understanding of how to reduce the effects of diabetes on their eyes. CONCLUSIONS: Study findings identified important links between financial resources and experiencing a vision problem and the adoption of preventive eye care in an urban African-American population.